Blood glucose changes in diabetic children and adolescents engaged in most common sports activities - Corigliano, Gerardo; Iazzetta, Nicolangelo; Corigliano, Marco; Strolli, Felice (Acta Biomedica Atenei Parmensis, 2006)
Circulating insulin levels decrease and substrate glycogenolysis-mediated conversion into glucose increases just a few minutes after normal subjects start exercising, but during sustained physical activity muscles massively utilize blood glucose, thus causing glycogenolysis to increase further until the end of the session. After that, in order to get liver and muscle glycogen stores up to pre-exercise levels again, blood glucose is mostly utilized, thus causing late-onset hypoglycaemia in the absence of any extra carbohydrate supply and rebound hyperglycaemia after a while. This and other patho-physiological mechanisms are dealt with in the present paper, and practical hints are provided to the clinician to cope with children-specific adaptation phenomena to exercise in t1DM.